An Important Cause of Tetraplegia: Cervical Spondylotic Myelopathy - Figen Tuncay; Fatmanur Aybala Koçak; Zeynep Karakuzu Güngör; Hatice Rana Erdem (Galenos Yayinevi, 2017)
Cervical spondylotic myelopathy is a neurological disorder caused by degenerative changes in the cervical spines emerging from spinal channel narrowing. This is the most common reason of spastic tetraplegia in later phases of life. In this case report, an elderly male patient with subclinical symptoms and having cervical spondylotic myelopathy causing sudden spastic tetraplegia was presented in the light of current literature.